Prescribing errors in paediatrics. Issue 5 (22nd April 2012) - Bowns, J; Andreas, A; Gill, A
Abstract : Objective: In 2007 the General Medical Council commissioned a research programme to explore the causes of prescribing errors made by Foundation trainee (FY1) doctors in relation to their medical education, the EQUIP study.1 This involved a prospective evaluation of the prevalence and nature of prescribing errors made by prescribers of all grades in 19 acute hospitals in North West England. Alder Hey pharmacists have continued to collect prescribing errors using this methodology to identify whether the error patterns in paediatrics differ from those identified in a mainly adult population. Method: The EQUIP data collection forms are used on one day per month to record any prescribing errors identified according to defined criteria. Data are collected on all new items prescribed, the prescribing stage (for example admission, during stay or discharge), the grade of prescriber and whether an error occurred. Full details of the actual error are recorded on a second form and the pharmacist allocates a potential severity according to predetermined criteria. Unfortunately an error validation panel similar to that used in the EQUIP study was not possible but one senior clinical pharmacist assessed all errors to establish validity and check the severity grading. This report includes all errors identified through this methodology during 2010. Results: Over the 12 data collection dates in 2010 a total of 3994 items were checked. 340 errors were detected, giving a mean error rate of 8.5 per 100 medication orders. This compares with a mean error rate of 8.9 per 100 medication orders in the EQUIP study. Similarly to the EQUIP study, The authors found that the grade of prescriber responsible for the highest rate of prescribing errors was the Foundation Year 2 doctors (11.3% Alder Hey, 10.3% EQUIP) and that FY1 produced a lower rate of prescribing errors (7.4% Alder Hey, 8.4% EQUIP). The most frequent error type in paediatrics was dosing errors which accounted for 26.8% of all errors. Omission of medication was found to occur in 12.6% of cases. This is in contrast to the EQUIP study which found that omissions accounted for 36% of errors and dosing errors 19.6%. Four errors (1.2%) were assessed as being potentially lethal, 18 (5.4%) as serious and 126 (37%) as significant. The EQUIP study found 1.7% of errors were potentially lethal, 5.6% serious and 53% significant. Conclusion: This study has shown that although the overall frequency and severity of errors in paediatrics are very similar to those in a mainly adult population, the types of errors are quite different. This information has been used locally to inform the content of tutorials and assessments so that prescribers are aware of common paediatric prescribing problems.